Influência da orientação corporal no desenvolvimento do controle de cabeça de lactentes - Lima-Alvarez, Carolina Daniel de (2012)
Head movements play an important role in typical motor development because they form the basis for the emergence of fundamental motor skills such as reaching and sitting. In addition, the head is the first part of the body to develop antigravity control, and serve as a frame for the organization of postural control. The aims of this longitudinal study were: 1) to provide information about the behavioral (frequency of head movement; proportion of head initial position to the right, left and midline; proportion of movement type sideto- midline, midline-to-side and side-to-side) and kinematics (amplitude of head movement: flexion, inclination and rotation; duration of the movement; mean angular velocity; peak velocity; deceleration index; number of movement unit; number of movement unit after peak velocity; mean duration of movement unit; mean duration of movement unit after peak velocity; duration of the longest movement unit) changes during the acquisition of head control in supine position; 2) to verify and to describe the age-related changes observed in the spatial-temporal organization of the head movement; 3) to verify e if different body orientations (unsupported supine; supported supine head supported and semi flexed approximately to 15° over an infant pillow; and supported reclined- head supported and semi flexed approximately and the body reclined to 20° with the horizontal plane) and if external head support can improve the alignment between head and trunk, thus turning the head movement more controlled and 4) to verify if the body orientation can facilitate the head movement in younger infants (from birth to two months), as they head movement are not as controlled as older infants. To this end, 17 infants were longitudinally assessed once a month. They were presented with a black and white card that was moved sideward in front of their face in all the conditions (unsupported supine, supported supine and supported reclined. Results of study 1, focused in the age-related effect of head movement showed that with age, particularly from two months onwards, the head was more often held at body midline. A larger amount of head movements and an increase in amplitude and speed of the head movement accompanied this change between two and three months. Kinematic analysis also showed that head movements were organized in movement units that increased in number until three months of age, but significantly decreased afterwards (especially the number of movement units after peak velocity). The results about body orientation manipulation, study 2, showed that the behavioral and kinematic analyses in the supported supine and supported reclined conditions, showed an increase in the proportions of head positions at the body midline and midline-to-side head movements in comparison to the unsupported supine condition. Further, a lower mean angular velocity and a prolonged duration of the head movement and its constituent movement units (including the longest movement unit) were observed in the supported supine and reclined conditions. The results suggest that the velocity profile became more symmetrical with age, especially after two months-old onwards, which is indicative for better and more efficient control of the head movements. Importantly, many of the differences only occurred when infants were younger than three months of age. In sum, vii the head movement became more fluent and well-organized through age, especially after three months. The external support of the head led to an improvement in the alignment of head and trunk, which promoted better-controlled head movements, especially in the younger infants. This suggests that neck muscle strength is an important limiting factor in the development of head movements.